Staging Inquiry: How Broadway Musicals Model Qualitative and Arts-Based Research Methodologies - McGill, Craig M. (Art/Research International)

(untitled) (University of Alberta, 2026)
This article explores how three musicals model rich sites of qualitative and arts-based research. Drawing on A Chorus Line, Tick, Tick… Boom!, and A Strange Loop, I analyze how each musical enacts distinct methodological approaches—including ensemble-based narrative inquiry, autoethnography, and performative ethnodrama. Grounded in a conceptual framework informed by arts-based research and Fenton’s (2021) ethnomusical libretto, the analysis draws on narrative truth (lived experience as knowledge), embodied knowledge (performance, voice, and movement as data), and recursive structure (looped, self-reflexive meaning-making) to examine how musicals produce and represent understanding through aesthetic form. The article includes a reflexive interlude, situating the researcher as both audience member and analyst, demonstrating how disciplinary lenses shape engagement with performance. Ultimately, I argue that musical theatre functions not merely as an object of study, but as a model for a methodological form of inquiry and research dissemination, one that challenges conventional boundaries of method, voice, and representation while extending arts-based research into public, affective, and performative spaces.